Descending necrotizing mediastinitis secondary to a retropharyngeal abscess in an adult - Moreira, Carla (2017)
Introduction: Necrotizing descending mediastinitis (NDM) represents a severe and rare form of mediastinal infection, which can be secondary to a contiguous dissemination of pharyngeal infections. Also infrequent, retropharyngeal abscess is associated with high complication and mortality rates, including NDM. Early diagnosis and treatment of these clinical entities represent a clinical challenge in hospital emergency.Case Report: A 58 year old female with no relevant background presented to the emergency department with fever, sore throat and neck pain. Computed tomography of the neck showed an extensive retropharyngeal abscess that rapidly progressed into the mediastinal space within 48 hours.Results: Treatment involved combined surgical approach by otolaryngology and cardiothoracic surgery performing transoral drainage of retropharyngeal abscess and anterior cervicotomy to approach the upper mediastinum. Prolonged intravenous antibiotic therapy also contributed to successful clinical improvement.Conclusion: Descending necrotizing mediastinitis is a potentially fatal entity which must be addressed early, in an aggressive and multidisciplinary way.